Penerapan Metode Nanopartikel Lipid Padat pada Masker Gel Peeloff Ekstrak Teripang Hitam (Holothuria atra) dan Uji Aktivitas Antioksidan - Deni Rahmat; Safira Nafisa; Catharina Maria Odilia (Fakultas Farmasi Universitas Pancasila, 2023)
Black Sea cucumbers (Holothuria atra) are a potential source of active metabolites such as flavonoids widely used for nutraceutical, pharmaceutical, and cosmeceutical products. The type of nanoparticle that is often used in cosmetics and skin products is Solid Lipid Nanoparticles (SLN). In this study, the SLN of black sea cucumber extract will be prepared in the form of a peel-off gel mask as an antioxidant. Black sea cucumbers were extracted using the maceration method, while SLN preparation used high-shear homogenization and freeze-drying methods. Crude extract and SLN were formulated into peel-off gels and then evaluated, including organoleptic, homogeneity, viscosity, pH, spreadability, drying time, tensile strength test, and antioxidant activity using the DPPH method. The IC50 values of blank (F1), peel-off gel extract (F2), and nanoparticle peel-off gel extract (F3) were each 600.8727 ± 0.43; 580.7849±0.7; and 592.76±0.55 µg/mL. In conclusion, the SLN method can be applied to the formulation of black sea cucumber extract nanoparticles. However, peel-off gel masks from the crude and nanoparticle extracts have very weak antioxidant activity.